Implementing the Green Economy Concepts in the Russian Far East: Environmental Preconditions - Mirzekhanova, Zoya Gavrilovna (Economy of Regions, 2020)
The implementation of “Eastern Policy” increases economic activity in the Russian Far East. According to this policy, it is necessary to create and develop territories of advanced development (TADs), taking into account modern development requirements and the green economy concepts. The paper emphasizes that the region’s the geographical location and the established economic structure determine certain environmental conditions for implementing the green economy model. From the environmental viewpoint, the study shows the current situation and the benefits of applying global scenarios while creating the Far Eastern TADs, considering development characteristics of the region and lessons learned from the green model application. The transition to the green economy contributes to rethinking regional development strategies that enable ecosystem approach to the economic activity. . Thus, it is necessary to adjust the shaping of TADs in the Far East. The research identifies environmental preconditions for the structural formation of TADs based on the modern development concepts and the region’s current situation. The analysis of the activities of 115 enterprises operating in the Far Eastern TADs demonstrates their industrial structure, as well as the organisations’ compliance with the priorities of the green economy. A significant share of the enterprises does not correspond to the concepts of the model due to the raw material specialization, underutilized resource potential, and ignoring the requirement to use green innovations. The research results are useful for solving the problem of sustainable development of the region in the context of global requirements, as well as for creating an adequate environmental policy.